Zuni origins : toward a new synthesis of Southwestern archaeology - Gregory, David A.; Wilcox, David R., 1944- (University of Arizona Press, 2007)
The Zuni are a Southwestern people whose origins have long intrigued anthropologists. This volume presents fresh approaches to that question from both anthropological and traditional perspectives, exploring the origins of the tribe and the influences that have affected their way of life. Utilizing macro-regional approaches, it brings together many decades of research in the Zuni and Mogollon areas, incorporating archaeological evidence, environmental data, and linguistic analyses to propose new links among early Southwestern peoples. The findings reported here postulate the differentiation of the Zuni language at least 7,000 to 8,000 years ago, following the initial peopling of the hemisphere, and both formulate and test the hypothesis that many Mogollon populations were Zunian speakers. Some of the contributions situate Zuni within the developmental context of Southwestern societies from Paleoindian to Mogollon. Others test the Mogollon-Zuni hypothesis by searching for contrasts between these and neighboring peoples and tracing these contrasts through macro-regional analyses of environments, sites, pottery, basketry, and rock art. Several studies of late prehistoric and protohistoric settlement systems in the Zuni area then express more cautious views on the Mogollon connection and present insights from Zuni traditional history and cultural geography. Two internationally known scholars then critique the essays, and the editors present a new research design for pursuing the question of Zuni origins. By taking stock and synthesizing what is currently known about the origins of the Zuni language and the development of modern Zuni culture, Zuni Origins is the only volume to address this subject with such a breadth of data and interpretations. It will prove invaluable to archaeologists working throughout the North American Southwest as well as to others struggling with issues of ethnicity, migration, incipient agriculture, and linguistic origins.